Pengaruh Indeks Pembangunan Manusia dan Jumlah Angkatan Kerja terhadap Pertumbuhan Ekonomi di Sumatera Utara Tahun 2017 – 2023 - Elsa Novri Regina; Joko Suharianto; Intan Febyanti; Mirna Salifah Siregar; Syaila Azzahraini Siregar (Universitas 45 Surabaya, 2025)
This research aims to analyze the influence of the Human Development Index (HDI) and the number of workforce employed on economic growth in North Sumatra Province during the 2017-2023 period. The research method used is a quantitative approach with multiple linear regression analysis. The data used is secondary data obtained from the Central Statistics Agency (BPS) and other related sources. The research results show that HDI and the number of working forces have a significant influence on economic growth in North Sumatra. Partially, HDI contributes positively to increasing economic growth, which reflects the importance of improving the quality of education, health and people's living standards. The size of the workforce also has a significant influence, but this needs to be balanced with increasing labor productivity. These findings provide important implications for policy makers to focus more on improving the quality of human resources and managing the number of armed forces in order to encourage sustainable economic growth.